The Secret of Generating the Lethal Blowpipe Dart Poison in Borneo - Herwig Zahorka (The Ethnobiological Society of Indonesia, 2005)
The blowpipe dart poison in Borneo is generally generated from the latex of rhe large .Antians toxicana tree, Moraceae. This latex contains a variety of toxic chemical compounds. The principal toxic agent rs a steroid glycoside known as -Antiacin. A lethal dose (LSO) is only about 0.1 mg per kg weight of a warm-blooded animal. To dehydrate the milky latex into a paste, a long carefully implemented procedure is essential because that steroid glycoside compound is extremely heat-sensitive. Therefore, the blowpipe hunters perform the dehydration of the latex with the assistance of a young leaf from the small Liataia spinosa palm. The leaf is formed into boat-shape to hold the latex at a carefully determined distance over a small flame for about one week. This is feasible because the young Licuala leaf is astonishingly fireproof and durable. This is the secret of generating the lethal poison. If the latex were heated at coo high temperature, the glycoside compound would crack and the toxicity would be lost.